2019
DOI: 10.1097/dss.0000000000001614
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Rich Plasma Augments Subcision in Atrophic Acne Scars: A Split-Face Comparative Study

Abstract: Platelet-rich plasma and subcision act synergistically to improve the appearance of acne scars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
2
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 13 publications
1
29
2
2
Order By: Relevance
“…All included studies were either a comparative, simple randomized, noncontrolled study, or a nonrandomized, controlled, before‐and‐after study . The included study characteristics are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All included studies were either a comparative, simple randomized, noncontrolled study, or a nonrandomized, controlled, before‐and‐after study . The included study characteristics are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
“…In a split‐face trial, Deshmukh et al reported 7 cases of postinflammatory hyperpigmentation (PIH) that occurred as a result of both PRP combined with subcision and subcision alone. These reactions occurred equally on both sides of each patient's face.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rolling acne scars responded best followed by boxcars (33.88%). [ 90 ] Bhargava et al [ 91 ] combined PRP with subcision and needling in a randomized study of 30 patients. Significantly more patients in the PRP group had >50% improvement in scars and the downtime was also less.…”
Section: P Latelet-rich P Lasma and mentioning
confidence: 99%
“…Já as cicatrizes faciais ocasionadas por acne afetam 75% dos pacientes. O plasma rico em plaquetas é uma nova opção de tratamento para o controle da acne e suas cicatrizes, devido às suas propriedades antimicrobianas, anti-inflamatórias e rejuvenescedoras (DESHMUKH;BELGAUMKAR, 2018).…”
Section: Introductionunclassified